Meteorites from meteor showers: A case study of the Taurids. (25th January 2013) - Brown, Peter; Marchenko, Valerie; Moser, Danielle E.; Weryk, Robert; Cooke, William
Abstract We propose that the Taurid meteor shower may contain bodies able to survive and be recovered as meteorites. We review the expected properties of meteorite‐producing fireballs, and suggest that end heights below 35 km and terminal speeds below 10 km s−1 are necessary conditions for fireballs expected to produce meteorites. Applying the meteoroid strength index (PE criteria) of Ceplecha and McCrosky (1976) to a suite of 33 photographically recorded Taurid fireballs, we find a large spread in the apparent meteoroid strengths within the stream, including some very strong meteoroids. We also examine in detail the flight behavior of a Taurid fireball (SOMN 101031) and show that it has the potential to be a (small) meteorite‐producing event. Similarly, photographic observations of a bright, potential Taurid fireball recorded in November of 1995 in Spain show that it also had meteorite‐producing characteristics, despite a very high entry velocity (33 km s−1). Finally, we note that the recent Maribo meteorite fall may have had a very high entry velocity (28 km s−1), further suggesting that survival of meteorites at Taurid‐like velocities is possible. Application of a numerical entry model also shows plausible survival of meteorites at Taurid‐like velocities, provided the initial meteoroids are fairly strong and large, both of which are characteristics found in the Taurid stream.